2022
DOI: 10.1016/j.ultrasmedbio.2021.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Imaging Acquisition Procedures for Evaluating the First Metatarsophalangeal Joint: A Scoping Review

Abstract: The aim of this scoping review was to investigate ultrasound imaging (USI) acquisition procedures and guidelines used to assess the first metatarsophalangeal joint (MTPJ). MEDLINE, CINAHL, AMED and SPORTDiscus were systematically searched in May 2021. Studies were included if they used grey-scale USI or power Doppler and reported a USI procedure to assess the first MTPJ. Screening and data extraction were performed by two independent assessors. The scoping review was reported in accordance with the Preferred R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Authors identified 50 open-ended items based on the participants free-text responses in Round 1. These items were combined with an additional 12 items generated from the authors’ recent systematic [ 25 ] and scoping reviews [ 26 ] to be considered in Round 2. Participants rated 62 items in Round 2, 23 items reached consensus (medians score of ≥70%), 21 items were considered ambiguous (achieved a median score between 51 and 69% agreement), and 18 items were excluded (median score ≤50%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Authors identified 50 open-ended items based on the participants free-text responses in Round 1. These items were combined with an additional 12 items generated from the authors’ recent systematic [ 25 ] and scoping reviews [ 26 ] to be considered in Round 2. Participants rated 62 items in Round 2, 23 items reached consensus (medians score of ≥70%), 21 items were considered ambiguous (achieved a median score between 51 and 69% agreement), and 18 items were excluded (median score ≤50%).…”
Section: Resultsmentioning
confidence: 99%
“…As it stands only two consensus-based guidelines exist to inform the US imaging acquisition procedure to assess the first MTPJ [ 16 , 51 ]. Despite this, there has been marked inconsistency in the application of guidelines across studies [ 26 ]. The 2001 EULAR guidelines included limited instructions on body position, transducer orientation and surfaces of the first MTPJ to scan (supine position for the dorsal scans and prone position for the plantar scans) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations